Les manuscrits araméens du Wadi Daliyeh et la Samarie vers 450-332 av. J.-C. - Dušek, Jan. (Culture and History of the Ancient Near East, 2007)
This book deals with the manuscripts from the Wadi Daliyeh (Samaria Papyri) written in Aramaic in the fourth century B.C.E. in the city of Samaria, in the last decades of the Persian period. The book contains a complete edition of the Wadi Daliyeh manuscripts, their new historical interpretation, and an analysis of their legal aspects. The historical interpretation sheds new light on the history of Samaria and its institutions in the Persian period, as well as on the history of the Persian province of Judaea. This book is particulary useful for historians of Palestine in the Second Temple period, for biblical scholars, and for scholars dealing with Near Eastern legal texts.